The assimilation of Greeks in the United States, by Evangelos C. Vlachos, First and second generation Greeks in Chicago, by George A. Kourvetaris and Family and mobility among second generation Greek-Americans, by Nicholas Tavuchis - Moskos, Charles (The Greek Review of Social Research, 1972)
[No abstract available]